91.7k views
4 votes
Factor -3/4 out of 3/2x - 9/4y

2 Answers

3 votes

Answer:

-3/4 x (-2x + 3y)

Explanation:

User Chefsmart
by
6.0k points
5 votes

Answer:


-(3)/(4) * (-2x +3y)

Explanation:

To factor out -3/4 out of that equation, multiply and divide by -3/4.

Say ;

=
(3)/(2)x -(9)/(4)y

=
((3)/(2)x -(9)/(4)y) * (-(3)/(4) )/(-(3)/(4))

Now, rearranging and making necessary commutations.

=
-(3)/(4) * ((3)/(2)x -(9)/(4)y) * (1 )/(-(3)/(4))

=
-(3)/(4) * (-2x +3y)

Factoring -3/4 we get an equation without any fractions

= -2x + 3y

User Xamenrax
by
5.3k points